Methods of Stealing Personal Data on Android using a Remote Administration Tool with Social Engineering Techniques - Ridwan Satrio Hadikusuma; Lukas Lukas; Epril M Rizaludin (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2023)
IT security is a significant concern of the internet because almost all communication occurs today. The purpose of testing personal data theft with the social engineering method is to ensure that the system and network on the user's Android have security holes to be hacked if the user is not aware of social engineering that allows data theft through the remote administration tool (RAT) which is accidentally downloaded on the Android User. Installing a RAT by applying social engineering is the possible and proper way to steal Android user privacy data. This study outlines some basic concepts of data theft, from recent call data and personal data to controlling Android users' cameras and microphones remotely.